Géographie et anthropologie. Deux regards complémentaires pour l’étude des territoires des populations traditionnelles d’Amazonie brésilienne - Collectif USART (EchoGéo)
Anthropology and geography share common interests such as space or territory. But, even if specialists from each of the two disciplines have used concepts derived from the other, common work on the same topics are scare. We show in this paper that the traditional communities of the Brazilian Amazon region are a very interesting object for such pluridisciplinary studies. Furthermore, the geographical/anthropological perspective is necessary if the objective is a full understanding of what is at stake within those social groups. Those arguments are at the core of the USART research team, and they also constitute the basis of our commitment with these populations, which goes beyond the simple scientific observation.